The Use of ISO 14001 Environmental Management Systems in the Process of Preparation and Provision of Environmental Insurance - Lemkowska, Malwina (Acta Universitatis Lodziensis. Folia Oeconomica, 2020)
The purpose of the research is to assess usefulness of the implemented and certified management systems for preparation and provision of insurance. Data was collected by means of non‑real‑time, time‑extended, text‑based online focus groups, obtained via Bulletin Board platform. Respondents were selected according to judgmental sampling, and were insurance sector experts. The template analyses of the interview transcript supported by a narrative approach were conducted. The research demonstrated that environmental insurance and ISO 14001 environmental management systems (EMSs) at present, remain in Poland almost entirely independent of each other. Representatives of insurance industry do not use the information about the system implementation while preparing and providing insurance cover. ISO 14001 EMSs present little credibility for insurance experts and according to the respondents, their implementation does not significantly and undoubtedly affect the level of the covered risk. Consequently, insurance buyers do not profit from insurance (lower premiums, improved insurance scope) resulting from the implementation of ISO 14001 systems. Industry representatives, however, use – albeit unconsciously – systemic documentation in the process of preparation and provision of insurance cover. They also examine systemic processes performed in the organisation at the stage of risk assessment. Improvement of credibility of certification process, based on profound cooperation between certification institutions and insurance industry may increase the importance of ISO 14001 EMSs for the process of preparation and provision of insurance cover.